COVID-19 vaccine hesitancy among health care worker-parents (HCWP) in Puducherry, India and its implications on their children: A cross sectional descriptive study. Issue 40 (22nd September 2022) - Sarkar, Pratik; Chandrasekaran, Venkatesh; Gunasekaran, Dhandapany; Chinnakali, Palanivel
Abstract: Background: Vaccine hesitancy affects immunization programs worldwide and can impact vaccine coverage and fight against Coronavirus disease 2019 (COVID-19) too. Objectives: Primary objectives: To find out the magnitude of COVID-19 vaccine hesitancy among the Health Care Worker Parents (HCWPs), the reasons for vaccine hesitancy, and their perceptions regarding COVID-19 vaccination of their children. Secondary objective: To analyze the clinic-socio-demographic correlates of COVID-19 vaccine hesitancy among HCWPs. Methods: This was a cross sectional descriptive study. Health care workers who are parents were invited to participate in the study. Details about COVID vaccination status, COVID-19 illness of HCWPS and family members and its outcomes, reasons for not getting vaccinated, willingness to vaccinate their children, reasons for not willing to vaccinate their children, their responses to vaccine hesitancy survey (VHS) questionnaire and Modified Oxford COVID-19 vaccine hesitancy scale (MOVHS) were collected and analyzed using descriptive statistics. Results: A total of 269 HCWPs participated in the study. Of the HCWPs, 97% had completed their COVID-19 vaccination schedule. Majority stated that they would vaccinate their children when it is available. Although majority of the responses were positive or towards agreement, there were some striking variations in the responses among some sections of HCWPs. Positive responses to the questionnaire were associated with higher self-vaccination and a decision to vaccinate their children. Conclusion: Vaccine hesitancy was less common among HCWPs in our study. A section of the HCWPs might be disproportionately more hesitant than others. Majority were in favor of vaccinating their children.